Pengaruh Kinerja Lingkungan, Biaya Lingkungan, Profitabilitas dan Tingkat Kepemilikan Pemerintah terhadap Carbon Emission Disclosure - Alviona, Adinda Vira; Saraswati, Erwin (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2025)
The extreme heat we've been seeing lately is because of the increase in carbon emissions into the atmosphere. One of the causes of carbon emissions is corporate activity. This study was done to find out how environmental performance, environmental costs, profitability, and government ownership levels affect carbon emission disclosure. The research sample consisted of state-owned enterprises (SOEs) selected using purposive sampling, comprising 120 data points from 2019 to 2023 using secondary data. The analysis technique employed multiple regression analysis. The results of the study indicate that environmental performance has a positive impact on increasing carbon emission disclosure, as good rankings boost companies' confidence to maintain or improve disclosure. Meanwhile, the level of government ownership has a negative impact on the level of corporate transparency regarding carbon emission information, as the government plays a dual role as both a shareholder and regulator. Factors related to finance, namely environmental costs and profitability, show ineffective results in promoting carbon emission disclosure. Both aspects do not prioritize their use for environmental sustainability programs. Based on the conclusions presented in this study, it is possible to understand the determining factors that encourage and hinder the level of corporate transparency, thereby enabling the production of an accurate basis for calculating the total national carbon emissions inventory.